A wind-blown bubble in the Central Molecular Zone cloud G0.253+0.016 - Henshaw, Jonathan D.; Krumholz, Mark R.; Butterfield, Natalie O; Mackey, Jonathan; Ginsburg, Adam; Haworth, Thomas J; Nogueras-Lara, Francisco; Barnes, Ashley T; Longmore, Steven N; Bally, John; Kruijssen, Diederik; Mills, Elisabeth A C; et al. (Monthly notices of the Royal Astronomical Society, 2022)
G0.253+0.016, commonly referred to as ‘the Brick’ and located within the Central Molecular Zone, is one of the densest (≈103-4 cm−3) molecular clouds in the Galaxy to lack signatures of widespread star formation. We set out to constrain the origins of an arc-shaped molecular line emission feature located within the cloud. We determine that the arc, centred on $\lbrace l_{0},b_{0}\rbrace =\lbrace 0{_{.}^{°}} 248,\, 0{_{.}^{°}} 018\rbrace$, has a radius of 1.3 pc and kinematics indicative of the presence of a shell expanding at $5.2^{+2.7}_{-1.9}$ $\mathrm{\, km\, s}^{-1}$. Extended radio continuum emission fills the arc cavity and recombination line emission peaks at a similar velocity to the arc, implying that the molecular gas and ionized gas are physically related. The inferred Lyman continuum photon rate is NLyC = 1046.0-1047.9 photons s−1, consistent with a star of spectral type B1-O8.5, corresponding to a mass of ≈12-20 M⊙. We explore two scenarios for the origin of the arc: (i) a partial shell swept up by the wind of an interloper high-mass star and (ii) a partial shell swept up by stellar feedback resulting from in situ star formation. We favour the latter scenario, finding reasonable (factor of a few) agreement between its morphology, dynamics, and energetics and those predicted for an expanding bubble driven by the wind from a high-mass star. The immediate implication is that G0.253+0.016 may not be as quiescent as is commonly accepted. We speculate that the cloud may have produced a ≲103 M⊙ star cluster ≳0.4 Myr ago, and demonstrate that the high-extinction and stellar crowding observed towards G0.253+0.016 may help to obscure such a star cluster from detection.
Published: 17 December 2021
Gesehen am 20.04.2022